The Impact of Technological Advancements on Impulse Buying Behavior in Shanghai's B2C E-commerce Sector - Michael, Evdokia (2024)
The thesis examines the influence of technological advancements on impulse buying behavior within Shanghai's B2C e-commerce sector. The study is prompted by the global importance of e-commerce and the trend of impulse purchases, with Shanghai as an example city for analysis. The insights may be applied to more general e-commerce contexts by looking at the dynamics of consumer behavior in this setting. The examination of impulsive buying patterns is guided by theoretical frameworks such as the Theory of Planned Behavior and the Stimulus-OrganismResponse model. Using quantitative methodology, the thesis seeks to evaluate the main causes and effects of impulsive purchasing, assess the contribution of technical advancements, and understand the impact of social and cultural aspects. In Shanghai's B2C e-commerce environment, the findings will provide recommendations for businesses and regulators on encouraging sustainable and responsible consumer habits using surveys and statistical data analysis.